Equilibrium Incentives in Oligopoly: Corrigendum - Fershtman, Chaim; Judd, Kenneth L (American Economic Review, 2006)
Proposition 5 in our paper dealt with the incentive equilibrium in differentiated product oligopoly. The proposition states that under linear demand and cost functions, the incentive equilibrium is such that managers are overcompensated at the margin for profits. Given the correction of equation (24) above, we need to add that this proposition holds only when A (ba)c. Note, however, that this condition has little impact on our analysis, since in our setting it is a necessary condition for having a duopolistic market in which both firms produce positive quantities while having nonnegative profits.